Hypercalcemia and Osteolytic Lesions as Presenting Symptoms of Acute Lymphoblastic Leukemia in Children: Case Report and Literature Review - Min Chen; Min Chen; Min Chen; Jiaqi Ni; Jiaqi Ni; Jiaqi Ni; Jiaqi Ni; Xiaoxi Lu; Xiaoxi Lu (Frontiers Media S.A., 2022)
Acute lymphoblastic leukemia (ALL) presenting with hypercalcemia and osteolytic lesions is rare and unusual in childhood. We report a case of a 13-year-old boy with ALL who presented with intermittent fever, nausea, vomiting, and increasing lower limb pain. Skeletal X-rays and CT scan showed severe osteolytic lesions of the skull and extremities. Physical examination revealed multiple inguinal lymph nodes. Laboratory tests demonstrated severe hypercalcemia (Ca > 3.49 mmol/L), decreased parathyroid hormone (PTH), and vitamin D level. Despite a normal complete blood count and the absence of circulating blasts, bone marrow biopsy revealed B-precursor ALL. Hypercalcemia was initially treated with intravenous isotonic sodium chloride and furosemide but the serum calcium level was not normalized. It was successfully managed with calcitonin and pamidronate afterward. Later, the child responded well to chemotherapy and continued with consolidation treatment. The clinical condition was stable, and the bone marrow revealed complete remission. This case indicated that hypercalcemia alone or combined with osteolytic lesions can be the only presenting symptom of ALL in children. Diagnostic errors may occur especially when combined with the absence of circulating blasts in the peripheral blood smear. Bone marrow aspiration should be considered to confirm the diagnosis.